Metoidioplasty: techniques and outcomes - Djordjevic, Miroslav L.; Stojanovic, Borko; Bizic, Marta (Translational Andrology and Urology, 2019)
Phalloplasty represents the latest step in female-to-male transitioning and still remains a great challenge for transgender surgeons. Since we have two options in this transitioning—metoidioplasty and total phalloplasty—the transgender surgeon has to fully inform the individual about all aspects such as surgical steps, outcomes, advantages and disadvantages, possible complications, and expectations. Total phalloplasty with the creation of a neophallus of a similar volume to that in genetic males, is a complex and multi-staged procedure. Many different tissues (i.e., flaps) can be used, and the ideal procedure is still not established. In contrast to the above complexities involved in total phalloplasty, metoidioplasty presents a simple and one-stage procedure for the creation of a neophallus from a hormonally enlarged clitoris. This technique is very promising for individuals who desire gender-affirmation surgery without having to undergo the difficult and multistage creation of a male-sized neophallus. Also, this technique prevents scarring to the extragenital region, making the final results more acceptable for transgender individuals. Our goal is to objectively present the techniques for metoidioplasty and to define their value based on postoperative results.